2004
DOI: 10.1038/sj.ejcn.1601855
|View full text |Cite
|
Sign up to set email alerts
|

Soyfood consumption and risk of glycosuria: a cross-sectional study within the Shanghai Women's Health Study

Abstract: Objective: To assess the association between soyfood intake and risk of glycosuria. Design and methods: A cross-sectional study was conducted among participants of the Shanghai Women's Health Study, a population-based cohort study of women aged 40-70 y. Information on usual intake of soyfoods was obtained at baseline survey through an in-person interview using a validated food-frequency questionnaire. Included in this study were 39,385 cohort members screened for diabetes at the baseline survey and free of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 20 publications
1
31
0
Order By: Relevance
“…A large-scale, cross-sectional study of Chinese women found that a higher intake of soy foods was associated with a lower risk of glycosuria among postmenopausal women with a low body mass index. 49 Our study has also noted an interaction effect between treatment groups and baseline FG. The largest differences in changes in FG between the intervention and placebo groups were noted among women with high baseline FG (9100 mg/dL).…”
Section: Glucose-lowering Effectmentioning
confidence: 79%
“…A large-scale, cross-sectional study of Chinese women found that a higher intake of soy foods was associated with a lower risk of glycosuria among postmenopausal women with a low body mass index. 49 Our study has also noted an interaction effect between treatment groups and baseline FG. The largest differences in changes in FG between the intervention and placebo groups were noted among women with high baseline FG (9100 mg/dL).…”
Section: Glucose-lowering Effectmentioning
confidence: 79%
“…Epidemiological studies indicated that habitual soy intake was inversely associated with diabetes risk [29,30]. Additionally, a cross-sectional study [31] reported that increased consumption of soy products decreased type 2 diabetes risk in overweight Japanese women; however, other studies have not detected a significant effect [32,33].…”
Section: Discussionmentioning
confidence: 97%
“…The consumption of soya foods (tofu and other soya products) was previously associated with a significantly reduced prevalence of glycosuria in 39 385 Chinese women aged 40-70 years without diabetes, especially postmenopausal women with BMI < 25 kg/m 2 (15) . Nanri et al reported a significant correlation between soya products and daidzein intake and a reduced cumulative incidence of type 2 diabetes among women with BMI > 25 kg/m 2 and postmenopausal women (16) .…”
Section: Discussionmentioning
confidence: 99%
“…A diet with soyanuts (12) and supplements with soya protein, fibre, isoflavone and other soya products improved glucose homeostasis in patients with type 2 diabetes (13,14) . An inverse association between soya food intake and the prevalence of glycosuria was also reported in postmenopausal non-obese Chinese women (15) . Furthermore, a recent prospective study in Japan showed that higher intake of soya products and isoflavones was associated with a decreased odds ratio of diabetes among overweight or postmenopausal women (16) .…”
mentioning
confidence: 99%